186k views
1 vote
If f(x) = 3x - 1 and g(x) = x + 2, find (f+g)(x).

A. 4x + 1
B. 2x - 1
C. 2x - 3
D. 3x-3​

2 Answers

4 votes

Given:

f(x) = 3x - 1

g(x) = x + 2

To Find:

(f+g)(x) = f(x) + g(x)

Step-by-step explanation:

By putting the values, we get

3x - 1 + x + 2

By simplifying the like terms, we get

3x + x - 1 + 2

= 4x + 1

Answer:

(f+g)(x) = 4x + 1

Therefore, A. 4x + 1 is the correct answer.

User Raldi
by
5.1k points
3 votes

Answer:


\boxed {\boxed {\sf A. \ 4x+1}}

Step-by-step explanation:

We are asked to find (f+g)(x). The question is essentially asking us to find the sum of f(x) and g(x).


(f+g)(x)=f(x)+g(x)

We know that f(x) equals 3x-1 and g(x) equals x+2. Substitute the values of the functions in.


(f+g)(x)=(3x-1)+(x+2)

Combine the like terms.

  • 3x and x are like terms (both have the variable "x"
  • -1 and 2 are like terms (both without variables, also known as constants)


(f+g)(x)=(3x+x)+(-1+2)


(f+g)(x)=(4x)+(1)=4x+1

(f+g)(x) is equal to 4x+1 and the correct answer is A.

User Acimutal
by
5.1k points